Evaluating Clinical Practice Guidelines Based on Their Association with Return to Work in Administrative Claims Data. (14th September 2015) - Roberts, Eric T.; DuGoff, Eva H.; Heins, Sara E.; Swedler, David I.; Castillo, Renan C.; Feldman, Dorianne R.; Wegener, Stephen T.; Canudas‐Romo, Vladimir; Anderson, Gerard F.
Abstract : Objective: To examine the association between non‐adherence to clinical practice guidelines (CPGs) and time to return to work (RTW) for patients with workplace injuries. Data Sources/Study Setting: Secondary analysis of medical billing and disability data for 148, 199 for shoulder and back injuries from a workers' compensation insurer. Study Design: Cox proportional hazard regression is used to estimate the association between time to RTW and receipt of guideline‐discordant care. We test the robustness of our findings to an omitted confounding variable. Data Collection: Collected by the insurer from the time an injury was reported, through recovery or last follow‐up. Principal Findings: Receiving guideline‐discordant care was associated with slower RTW for only some guidelines. Early receipt of care, and getting less than the recommended amount of care, were correlated with faster RTW. Excessive physical therapy, bracing, and injections were associated with slower RTW. Conclusions: There is not a consistent relationship between performance on CPGs and RTW. The association between performance on CPG and RTW is difficult to measure in observational data, because analysts cannot control for omitted variables that affect a patient's treatment and outcomes. CPGs supported by observational studies or randomized trials may have a more certain relationship to health outcomes.